Efficacy of high-pitch CT protocols for radiation dose reduction. (19th September 2016) - Guberina, N; Lechel, U; Forsting, M; Ringelstein, A
Abstract: Various strategies have been developed to reduce radiation exposure of patients in CT examinations. The aim of this study was to evaluate the efficacy of high pitch in representative CT protocols examining lung embolism. We performed thermoluminescence measurements with an anthropomorphic phantom exposing it to CT algorithms for lung embolism in a 128-multislice, dual-source CT scanner: a standard CT protocol (sCT) and a CT protocol with a high pitch (+ F). Radiation doses for both CT algorithms were compared and the dose reduction potential of high pitch for individual organs was evaluated. As expected, the +F mode reduced the effective dose and organ doses in the primary beam of radiation (namely, lung, bone marrow, heart, breast, skin and skeleton) compared with sCT by up to 52% for an equivalent image quality. On the contrary, for organs at the margin of the primary beam (thymus, thyroid, liver, pancreas, kidneys, colon and small intestine), the +F mode reduced effective radiation doses by only 0–30%, compared with sCT. The dose reduction potential of the +F mode greatly depends on the position of the organ in the scan field. While for organs in the primary beam + F leads to a considerable dose reduction, it is less effective for tissues at the margin of the scanned area.